Liquid mixtures separation and heat consumption in the process of distillation - M. K. Zakharov; A. V. Egorov; A. A. Podmetenny (Тонкие химические технологии, 2021)
Objectives. The aim of this study is to investigate different distillation modes of a binary ideal mixture and determine how various factors affect heat consumption in the column boilers. In addition, it intends to assess the difficulty of separating mixtures. Our research is based on analyzing the characteristics of vapor-liquid equilibrium.Methods. To conduct our study, we used a graphic-analytical tool to calculate the distillation process of a binary mixture and mathematical models based on the Aspen Plus software package along with DSTWU, RadFrac, and the Sensitivity module. We also used the Peng-Robinson equation (PENG-ROB) to determine the liquid-vapor equilibrium.Results. We employed the graphical method and mathematical models to obtain the operation parameters of two column variants for the distillation of binary ideal benzene-toluene mixtures. In each variant the initial mixture contained the same amount of the low- and high-boiling component. The number of plates in the column sections, reflux ratio, energy consumption, and indicators of internal energy saving were determined.Conclusions. Study results show that using the coefficient of the component distribution between the vapor and liquid phases is a promising method for preliminary assessments of the separation difficulty and measurements of the expected heat consumption in the boilers of columns. Comparison studies showed that the heat consumption in the boiler decreases as the internal energy saving in the columns increases.